Analisis Reaksi Pasar Modal terhadap Peristiwa Pelantikan Prabowo-Gibran sebagai Presiden dan Wakil Presiden Indonesia 2024 (Event Study pada Indeks LQ45 di Bursa Efek Indonesia) - Marcella Zalianty (Fakultas Ekonomi dan Bisnis, 2026)
The capital market is often used as a benchmark for national economies in several countries, where capital market progress is directly correlated with accelerated economic growth. The capital market itself is divided into two main functions: economic and financial. The latter provides investors with opportunities to achieve returns commensurate with their investment activities. However, investment in the capital market also carries significant uncertainty. Therefore, the role of information is crucial in this environment. The inauguration of the President and Vice President of Indonesia in 2024 is one source of external information that has the potential to influence market reactions. The indicators used in this study are abnormal returns, trading volume activity, and security return variability. This study employs a quantitative research approach with an event study approach. The population is comprised of companies listed on the IDX30. The sample was selected using a purposive sampling technique, resulting in 38 companies for study. The data used is secondary data in the form of daily stock price data obtained from the official IDX website. The analytical tools used to test the hypotheses in this study are the paired sample t-test and the Wilcoxon signed rank test using SPSS. The results of the study show that (1) a significant difference was found in the abnormal return values before and after the event. (2) a significant difference was found in the trading volume activity values before and after the event. (3) no significant difference was found in the security return variability values.
Approved by Teddy
Keywords: abnormal return; trading volume activity; security return variability; capital market